Pengintegrasian Nilai Karakter Cinta Tanah Air dalam Pembelajaran Tematik di SD - Annur, Risnayanti (Indonesian Journal Publisher, 2024)
This journal explores the integration of the character value of Love for the Homeland in thematic learning at the Elementary School (SD) level. The research aims to understand the impact of integrating these values on students' character development. The research methods involve classroom observations, interviews with teachers, and curriculum document analysis. The results indicate that thematic learning with a focus on love for the homeland enhances students' understanding of national values. Additionally, students show improvements in positive attitudes, cooperation, and responsibility towards the surrounding environment. The practical implication of this journal emphasizes the importance of supporting teachers in integrating national character values into the curriculum, shaping a generation that loves their homeland and possesses a strong national identity. This study contributes to a practical understanding of implementing character values in the context of thematic learning at the elementary school level.